2001
DOI: 10.1002/ana.1257
|View full text |Cite
|
Sign up to set email alerts
|

Fluoxetine modulates motor performance and cerebral activation of patients recovering from stroke

Abstract: In order to determine the influence of a single dose of fluoxetine on the cerebral motor activation of lacunar stroke patients in the early phase of recovery, we conducted a prospective, double-blind, crossover, placebo-controlled study on 8 patients with pure motor hemiparesia. Each patient underwent two functional magnetic resonance imaging (fMRI) examinations: one under fluoxetine and one under placebo. The first was performed 2 weeks after stroke onset and the second a week later. During the two fMRI exami… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
187
2
11

Year Published

2002
2002
2015
2015

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 341 publications
(203 citation statements)
references
References 43 publications
3
187
2
11
Order By: Relevance
“…In accordance, LTD is facilitated in animal models of depression, which was prevented by chronic application of the selective serotonin reuptake inhibitor (SSRI) fluvoxamine (Holderbach et al, 2007). Besides depression, several studies have demonstrated that SSRIs improve motor functions in stroke patients (Chollet et al, 2011;Dam et al, 1996;Pariente et al, 2001) and in healthy individuals (Loubinoux et al, 1999;Loubinoux et al, 2002a;Loubinoux et al, 2002b;Loubinoux et al, 2005). Again, the physiological basis for this effect might be the impact of serotonin on plasticity.…”
Section: Introductionmentioning
confidence: 98%
“…In accordance, LTD is facilitated in animal models of depression, which was prevented by chronic application of the selective serotonin reuptake inhibitor (SSRI) fluvoxamine (Holderbach et al, 2007). Besides depression, several studies have demonstrated that SSRIs improve motor functions in stroke patients (Chollet et al, 2011;Dam et al, 1996;Pariente et al, 2001) and in healthy individuals (Loubinoux et al, 1999;Loubinoux et al, 2002a;Loubinoux et al, 2002b;Loubinoux et al, 2005). Again, the physiological basis for this effect might be the impact of serotonin on plasticity.…”
Section: Introductionmentioning
confidence: 98%
“…17,26 One explanation may be assessment of lower extremity function in the present study, where direct cortical projections to lower versus upper extremity motor pools in humans are more limited, such that increased motor cortical excitability may not sufficiently increase descending commands to increase peak force output. However, patients with incomplete SCI demonstrate increases in strength, 30 suggesting that differences in tested populations may also contribute.…”
Section: Minimal Changes In Single Mvcs or Clinical Assessmentsmentioning
confidence: 89%
“…Previous data suggest that selective serotonin reuptake inhibitors (SSRIs) may mitigate weakness 17 and improve function poststroke. 18,19,20 In general, SSRIs facilitate 5-hydroxytryptamine (serotonin) (5-HT) transmission by decreasing presynaptic sequestration in axon terminals originating primarily from brainstem (raphe) projections.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…But also the effects of drugs can be studied. Application of a single dose or a 1-week treatment with a selective serotonin-reuptake inhibitor increases the activeability of the motor system, including M1, measured with fMRI in normal subjects (102), as well as in stroke patients correlating with improvement of function (103).…”
Section: Clinical Applications Of Fmrimentioning
confidence: 99%